Assessment on tunnel lining to ensure stability in soft ground - Mohd. Muhtar, N. I. S. (2019)
Soft ground tunnelling describes as additional measures that are needed to be taken as it has been associated with settlement due to changes of stress and strength of the soil induced by tunnelling. Segmental tunnel lining is a structure used to support the ground and to have allowable movement due to soil stress redistribution. The research will be focusing on the type of modelling, structure parameter of the tunnel, pressure upon the tunnel lining and relationship with the induced ground settlement. Tunnel modelling was done in three dimensional (3D) modelling using ABAQUS software; of tunnel as parameter. This paper will discuss the effect of jack forces to the global behavior of the tunnel in order to support the surrounding load, thus be able to handle the tunnel-soil reaction without any visible or critical deformation, so that the tunnel can be used in the stable condition. A stand-alone ring method together with all-in-once method was used to simulate the Singapore MRT Circle Line 3 (CCL3). In the findings, when the tunnel lining thickness is reduced, the settlement of the ground surface is increased. Jack forces is also one of the reason of the tunnel to distort and the effect is more visible on the rings with reduced thickness compared to original thickness of the tunnel lining.